Survival dynamics of stick insect and the impact of environmental factors on natural fungal infection during the rainy season - Min, Donggyu; Shin, Soobin; Lee, Noh-Hyun; Baek, Min Jeong; Park, Sun-Jae; Kim, Kwang-Hyung; Son, Hokyoung; Jung, Jong-Kook (Frontiers in Microbiology, 2024)
Phasmatodea, commonly known as stick insects, are recognized as noteworthy pests globally, impacting agriculture and forest ecosystems. Among them, the outbreak of Ramulus mikado has emerged as a notable concern in East Asian forests. Recently, Metarhizium phasmatodeae has been identified as utilizing stick insects as hosts. We have observed evidence of this entomopathogenic fungus infecting stick insects. Given the increase in these occurrences during the rainy period, this study investigated the relationship between the survival of R. mikado and the M. phasmatodeae infection during the rainy seasons of 2022 and 2023, while also examining environmental factors. No infections were detected in specimens collected in June before the rainy season, but from July onwards, both the mortality of R. mikado and the fungal infection substantially increased. By the last sampling date of each year, 75% (2022), 71.4% (2023) of the specimens were infected, and over 90% of the total individuals succumbed as a result. Fungi isolated from deceased R. mikado were successfully identified as M. phasmatodeae using morphological and taxonomic approaches. Various statistical analyses, including principal component analysis and modeling, revealed a robust association between fungal infection and the survival of stick insects. The results highlight the correlation between mass deaths of stick insects and fungal infection, particularly during the summer rainy season. These findings offer valuable insights for forecasting R. mikado population in the upcoming year and developing effective pest control strategies.